BCL3-PVRL2-TOMM40 SNPs, gene-gene and gene-environment interactions on dyslipidemia - Miao, Liu; Yin, Rui-Xing; Pan, Shang-Ling; Yang, Shuo; Yang, De-Zhai; Lin, Wei-Xiong (Scientific reports, 2018)
Little is known about the association of the BCL3-PVRL2-TOMM40 SNPs and dyslipidemia. This study was to detect 12 BCL3-PVRL2-TOMM40 SNPs, gene-gene and gene-environment interactions on dyslipidemia in the Chinese Maonan population. Genotyping was performed in 1130 normal and 832 dyslipidemia participants. Generalized multifactor dimensionality reduction was used to screen the best interaction combination among SNPs and environmental exposures. Allele and genotype frequencies of the detected SNPs were different between the two groups ( P < 0.05–0.001). Association of the 12 SNPs and serum lipid levels was observed ( P < 0.004–0.001). Multiple-locus linkage disequilibrium was not statistically independent in the population ( D’ = 0.01–0.98). The dominant model of rs8100239 and rs157580 SNPs, several haplotypes and G × G interaction haplotypes contributed to a protection, whereas the dominant model of rs10402271, rs3810143, rs519113, rs6859 SNPs, another haplotypes and G × G interaction haplotypes revealed an increased morbidity function ( P < 0.05–0.001). There were significant three-locus model involving SNP-SNP, SNP-environment, haplotype-haplotype interactions ( P < 0.05–0.001). The subjects carrying several genotypes and haplotypes decreased dyslipidemia risk, whereas the subjects carrying other genotypes and haplotypes increased dyslipidemia risk. The BCL3-PVRL2-TOMM40 SNPs, gene-gene and gene-environment interactions on dyslipidemia were observed in the Chinese Maonan population.